Sensitivity Analysis for Thermal Stress and Creep Problems - HISADA, Toshiaki; NAKAMURA, Kazuhiro; CHEN, Xian; MORI, Masahiko (Transactions of the Japan Society of Mechanical Engineers Series A, 1999)
In this work, a finite element sensitivity analysis method for thermal stress and creep problems is proposed. The method is characterized by the so-called semi-analytical direct differentiation approach, i.e., the formulation is based on the direct differentiation but the variation of internal force due to the perturbation of design parameters is evaluated numerically. Since the corresponding subroutine of an existing finite element analysis code may be used, it is unnecessary to manipulate the adopted constitutive relation at sensitivity analysis stage. Thus, the proposed method can be applied for various temperature and time dependent problems. The effectiveness of the method is examined through a couple of numerical examples.